USING SQuaRE STANDARDS WITH TESTING SOFTWARE PROVISION IN THE ARMED FORCES OF UKRAINE - Alexander V. Ryzhkov; Marina A. Gerashchenko; Ruslan D. Barvinok; Fyodor V. Yermolenko (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
A series of international standards ISO / IEC 25000-25099, which regulate the quality of software products, is considered. It is determined that the standards have always played a special role for the telecommunications industry, since they are the key to the interoperability of various technologies: computer systems, communications and signaling, software and multimedia systems. In addition, the process of quality assurance in the development of software and evaluation during testing for the needs of the Armed Forces of Ukraine should be clearly regulated by the relevant government standards. It is shown that the standards under consideration supplement existing quality standards of software, combine existing standards or specify them. They provide coordination of the methodology for measuring and assessing the quality of software products.